사회적 지지가 중소도시 노인의 우울에 미치는 영향 - 김정유(Jung-Yoo Kim); 최유석(Youseok Choi) (한국콘텐츠학회 논문지, 15(4), 2015)
Using 492 older people in Chuncheon, this study examines whether social support is associated with depression of older people. Findings show that stress is positively associated with depression. Social support is negatively related to depression of older people. Analysis on the sources of social support reveals that all of the supports from families, friends, and important others are negatively associated with depression of the elderly. However, buffering effects of social support is not confirmed. Depression of older people is also associated with gender, household type, economic activity participation, and chronic diseases. Based on the findings, this study provides suggestions to prevent depression of older people and future research agenda. 이 연구에서는 강원도 춘천시에 거주하는 65세 이상 노인 492명을 대상으로 설문조사한 결과를 이용하여, 사회적 지지가 노인 우울과 어떠한 관련을 맺는지를 밝히고자 하였다. 분석결과, 노인의 스트레스 수준이 높을수록 우울 수준이 높았으며, 사회적 지지가 높을수록 우울 수준은 낮은 것으로 나타났다. 사회적 지지의 하위영역별(가족의 지지, 친구의 지지, 중요한 타인의 지지) 분석에서도 모두 지지 수준이 높은 노인의 경우, 우울 수준이 낮은 것으로 나타났다. 그러나 스트레스가 우울에 미치는 영향을 완화하는 사회적 지지의 스트레스 완충효과는 지지되지 않았다. 또한 우울 수준은 성별, 가구형태, 경제활동 여부, 만성질환 유무에 따라 유의미한 차이를 보였다. 연구결과를 기반으로 노인 우울 예방과 관련된 시사점과 향후 연구방향을 제안하였다.